2020
DOI: 10.4149/neo_2020_190709n609
|View full text |Cite
|
Sign up to set email alerts
|

SKA2 promotes proliferation and invasion of hepatocellular carcinoma cells via activating the β-catenin signaling pathway

Abstract: Spindle and kinetochore associated complex subunit 2 (SKA2) is a part of the spindle and kinetochore associated (SKA) complex, which has been reported in various cancers, including the breast cancer, lung cancer, and glioma. However, its role remains unclear in hepatocellular carcinoma (HCC). Our study found that SKA2 mRNA levels and immunohistochemistry staining were significantly increased in HCC tissues, compared with normal tissues. The role of SKA2 in cell proliferation and invasion was also determined. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Dysregulation of SKA2 has also been reported in past studies. Wang et al 35 revealed the apparent upregulation of SKA2 in hepatocellular carcinoma tissues, confirming that SKA2 had promotion effects on tumor cell metastasis. Zhuang et al 36 also uncovered that SKA2 combined with cyclic-AMP response binding protein and contributed to the proliferation of renal cell carcinoma cells and tumor growth in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 88%
“…Dysregulation of SKA2 has also been reported in past studies. Wang et al 35 revealed the apparent upregulation of SKA2 in hepatocellular carcinoma tissues, confirming that SKA2 had promotion effects on tumor cell metastasis. Zhuang et al 36 also uncovered that SKA2 combined with cyclic-AMP response binding protein and contributed to the proliferation of renal cell carcinoma cells and tumor growth in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study reported that the mRNA level and immunohistochemical staining of SKA2 were significantly increased in HCC tissues compared with normal tissues ( 17 ). Due to the direct targeting of miR-140-3p to SKA2, overexpression of SK2 could partially suppress the inhibitory effect of miR-140-3p restoration in breast cancer cells ( 18 ).…”
Section: Discussionmentioning
confidence: 99%